2013
DOI: 10.1039/c3ta12592k
|View full text |Cite
|
Sign up to set email alerts
|

Direct extreme UV-lithographic conversion of metal xanthates into nanostructured metal sulfide layers for hybrid photovoltaics

Abstract: We present a versatile strategy toward the preparation of nanostructured metal sulfide layers, which exploits the photosensitivity of metal xanthates as a powerful tool for lithographic structuring. Using extreme ultraviolet interference lithography (EUV-IL), we successfully realized well-defined column and comb nanostructures. This approach provides new pathways to fabricate highly ordered structured metal sulfide layers with periodicities far below 100 nm for potential application in hybrid solar cells. © 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…The attractive properties of metal xanthates, like their usually good stability (also in solution), relatively low decomposition temperature (below 200°C) and simplicity to tailor solubility and decomposition behavior by variation of their organic side chains, have ensured that they are widely employed in the preparation of various metal sulfide nanomaterials [35][36][37][38][39][51][52][53][54][55][56][57][58][59][60].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The attractive properties of metal xanthates, like their usually good stability (also in solution), relatively low decomposition temperature (below 200°C) and simplicity to tailor solubility and decomposition behavior by variation of their organic side chains, have ensured that they are widely employed in the preparation of various metal sulfide nanomaterials [35][36][37][38][39][51][52][53][54][55][56][57][58][59][60].…”
mentioning
confidence: 99%
“…Far less explored is the conversion of metal xanthates to metal sulfides at room temperature by photochemically induced decomposition using UV irradiation [56,57] or direct chemical reaction with primary amines. In this latter study, we have recently demonstrated that the conversion of copper and indium xanthates into CuInS 2 nanocrystals at room temperature in the presence of oleylamine proceeds via a reaction mechanism different to the Chugaev elimination [58].…”
mentioning
confidence: 99%
“…While the chemistry of metal xanthates has been the subject of study for many years, driven by applications in both analytical chemistry and metal extraction (Rao, 1971;Magee, 1973;Donaldson, 1976;Rao and Ramakrishna, 2003), recent years have seen a renaissance in the area resulting from the use of metal xanthates as single-source precursors (SSPs) to metal sulphide materials (Nair et al, 2002;Koh et al, 2003;Han et al, 2007;Clark et al, 2011;Liu et al, 2011;Rath et al, 2013;Kociok-Köhn et al, 2014). Remarkably, despite reports of ca.…”
Section: Introductionmentioning
confidence: 96%
“…Their ease of synthesis, general aerobic stability and, particularly, their facile decomposition via a Chugaev mechanism (Tschugaeff, 1900), thus affording low deposition temperatures, have attracted the interest of scientists as single-source precursors to a variety of sulfide-based materials (Bessergenev et al, 1998;Nair et al, 2002;Koh et al, 2003;Barreca et al, 2005;Han et al, 2007;Clark et al, 2011;Liu et al, 2011;Rath et al, 2013;Kociok-Köhn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%